2018
DOI: 10.3389/fcimb.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Novel Highly Pathogenic Avian Influenza A (H5N1) Virus Infection on Migrating Whooper Swans Fecal Microbiota

Abstract: The migration of wild birds plays an important role in the transmission and spread of H5 highly pathogenic avian influenza (HPAI) virus, posing a severe risk to animal and human health. Substantial evidence suggests that altered gut microbial community is implicated in the infection of respiratory influenza virus. However, the influence of H5N1 infection in gut microbiota of migratory birds remains unknown. In January 2015, a novel recombinant H5N1 virus emerged and killed about 100 migratory birds, mainly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Additionally, we identified differentially abundant genera across six phyla. The occurrence of some highly abundant bacterial genera in previous studies of migratory species (Lewis et al., 2016, 2017; Risely et al., 2018; Zhao et al., 2018) were common in both migrant and resident barn swallows (e.g., Enterococcus , Escherichia / Shigella , Lactococcus ), but in line with findings in the above studies, we found significantly greater abundance of the genera Catellicoccus , Clostridium_sensu_stricto_1 , Citrobacter , Corynebacterium , Fusobacterium , Lactobacillus , Leuconostoc , Mycoplasma , Romboutsia , Staphylococcus and Turicibacter in migrants ( deseq2 , Table ). There were few overlaps between the barn swallows in our study and the passerines studied by Lewis et al.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Additionally, we identified differentially abundant genera across six phyla. The occurrence of some highly abundant bacterial genera in previous studies of migratory species (Lewis et al., 2016, 2017; Risely et al., 2018; Zhao et al., 2018) were common in both migrant and resident barn swallows (e.g., Enterococcus , Escherichia / Shigella , Lactococcus ), but in line with findings in the above studies, we found significantly greater abundance of the genera Catellicoccus , Clostridium_sensu_stricto_1 , Citrobacter , Corynebacterium , Fusobacterium , Lactobacillus , Leuconostoc , Mycoplasma , Romboutsia , Staphylococcus and Turicibacter in migrants ( deseq2 , Table ). There were few overlaps between the barn swallows in our study and the passerines studied by Lewis et al.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, we identified differentially abundant genera across six phyla. The occurrence of some highly abundant bacterial genera in previous studies of migratory species (Lewis et al, 2016(Lewis et al, , 2017Risely et al, 2018;Zhao et al, 2018) were common in both migrant and resident barn swallows (e.g.,…”
Section: Differences In Microbial Communities Between Migrants and mentioning
confidence: 89%
See 3 more Smart Citations